2011
DOI: 10.17221/4272-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Metals as a cause of oxidative stress in fish: a review

Abstract: ABSTRACT:This review summarizes the current knowledge on the contribution of metals to the development of oxidative stress in fish. Metals are important inducers of oxidative stress in aquatic organisms, promoting formation of reactive oxygen species through two mechanisms. Redox active metals generate reactive oxygen species through redox cycling, while metals without redox potential impair antioxidant defences, especially that of thiol-containing antioxidants and enzymes. Elevated levels of reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
137
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 319 publications
(144 citation statements)
references
References 63 publications
(73 reference statements)
4
137
1
2
Order By: Relevance
“…On the other hand, no significant change in LPx levels in the selected tissues of fishes exposed to 1/10 th concentration of 100µg/L AgNPs might indicate a counter active mechanism of intrinsic antioxidant system. Though, antioxidant enzymes were not determined in the present study, it is well known that antioxidant enzymes play an important role during alterations in pro-oxidant and/or redox changes (22). One of the important findings of the present study (see section 2.4.2) suggests that 1/10 th concentration of 100µg/L AgNPs reversed the changes induced by A. hydrophila on activity levels of oxidative enzymes in the selected tissues of fishes.…”
Section: Discussionsupporting
confidence: 43%
“…On the other hand, no significant change in LPx levels in the selected tissues of fishes exposed to 1/10 th concentration of 100µg/L AgNPs might indicate a counter active mechanism of intrinsic antioxidant system. Though, antioxidant enzymes were not determined in the present study, it is well known that antioxidant enzymes play an important role during alterations in pro-oxidant and/or redox changes (22). One of the important findings of the present study (see section 2.4.2) suggests that 1/10 th concentration of 100µg/L AgNPs reversed the changes induced by A. hydrophila on activity levels of oxidative enzymes in the selected tissues of fishes.…”
Section: Discussionsupporting
confidence: 43%
“…ROS released from neutrophils, macrophages and endothelial cells in the vasculature are taken up by mammal erythrocytes (Aoshiba et al 1999;Nagababu and Rifkind 1998;Rifkind et al 1997). Moreover, studies have shown that the pollutants can stimulate ROS production in aquatic organisms (Kaptaner et al 2014;Sevcikova et al 2011;Xu et al 2012). This pool of ROS could impair the function of erythrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione S-transferases (GSTs) are involved in defense mechanism against xenobiotics and heavy metals (Stohs & Bagchi 1995). There are two types of heavy metals which are redox active metals and metals without redox (Sevcikova et al 2011). Redox active metals induced oxidative stress by altering redox cycling in the cells, which leads to glutathione reduction and elevation of antioxidant enzymes such as SOD, CAT and GPx.…”
Section: Introductionmentioning
confidence: 99%